Business Excellence Driven by Innovation Management - Ildiko-Csilla TAKACS (Communications of International Proceedings, 2021)
Innovation management is transforming the pace of business and accelerates emerging market changes supporting the principal strategic factors that can start successful advances, therefore the importance of innovative strategies have a central position and are responsible for the corporations’ business excellence. The top pioneering companies prioritise years of organizational performance and are uniquely qualified to inspire and enhance innovation because innovation is central to core values and creative leadership. The objective of this paper is to underline the prominence of innovation management as a principal strategic scheme in order to support the hypothesis that innovative strategies have vital impacts on the business excellence of competitive corporations. Innovation management is profoundly established in the revolutionary organization of global competitiveness, thus organisational merit will be achieved by companies which can react quickly to new market conditions and customer needs, and which constantly look for creative and original solutions to complex challenges. The principal accomplishments for distinctive economic sustainability in achieving and improving business excellence are novel innovative mind-sets and state-of-the-art research & design expenditure. The methodology used encompasses empirical research based on qualitative methods, outlining the significant innovative strategies towards more effective procedures and business excellence. All gathered data are analysed in a case study to imply excellent business models and determine the necessity for visionary leadership strategies. The results show which the strongest and weakest factors can be when devising innovative variabilities and emphasise the role of strategic innovations that are flexible and adaptable to dynamic sustainability and business excellence.
Keywords: Innovation Management; Competitive Strategies; Business Excellence